Case report: Efficacy of tofacitinib in the treatment of generalized pustular psoriasis - Wang, Xian; Zhang, Mei; He, Ming; Tang, Ting (Frontiers in Medicine, 2025)
Generalized pustular psoriasis (GPP) is a rare and potentially life-threatening autoimmune inflammatory skin disease. Tofacitinib is a non-selective, first-generation Janus kinase (JAK) inhibitor. Currently, both domestic and international reports regarding the use of tofacitinib mainly have primarily focused on the treatment of psoriasis vulgaris and psoriatic arthritis. As GPP is a rare skin disease, reports on the use of tofacitinib in the treatment of GPP are rare. This report presents a case of severe GPP that was effectively treated with tofacitinib. This case suggests that this non-selective JAK inhibitor, which has strong anti-inflammatory effects, could serve as an effective treatment option for cases of acute exacerbation of GPP, with a good safety profile.